2012
DOI: 10.1002/lary.23325
|View full text |Cite
|
Sign up to set email alerts
|

Reducing nasal morbidity after skull base reconstruction with the nasoseptal flap: Free middle turbinate mucosal grafts

Abstract: Introduction The nasoseptal flap provides hearty, vascularized tissue for reconstruction of Expanded Endonasal Approaches (EEA); however, it produces donor site morbidity due to exposed cartilage. Mucosalization of the septum requires 12 weeks, multiple debridements, and frequent saline rinses. This study addresses the reduction of nasal morbidity by grafting middle turbinate mucosa onto the exposed septum. Methods 15 patients undergoing EEA of the ventral skull base were prospectively enrolled. In seven cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 29 publications
(42 reference statements)
0
72
0
Order By: Relevance
“…Kimple et al described the use of a free mucosal graft harvested from a resected middle turbinate to graft the anterior septal cartilage of the NSF donor site. 15 Kasemsiri et al reported the use of a "reverse flap" in which an anteriorly based posterior septal mucosa flap of the septectomy site was rotated 180 degrees to the opposite side to cover the bare anterior septal cartilage.…”
Section: -14mentioning
confidence: 99%
See 3 more Smart Citations
“…Kimple et al described the use of a free mucosal graft harvested from a resected middle turbinate to graft the anterior septal cartilage of the NSF donor site. 15 Kasemsiri et al reported the use of a "reverse flap" in which an anteriorly based posterior septal mucosa flap of the septectomy site was rotated 180 degrees to the opposite side to cover the bare anterior septal cartilage.…”
Section: -14mentioning
confidence: 99%
“…8 With the absence of native mucosa with its mucociliary function, the stagnant blood and secretions on the exposed cartilage create a nidus for crusting which may lead to patient discomfort from nasal fullness, pain, poor nasal airflow, propensity for infection, and need for frequent debridements. 15 Several studies have investigated the sinonasal morbidity associated with use of the NSF with conflicting results. Hanson et al found significant endoscopy score differences in postoperative patients after NSF at 90 days after surgery; however, no differences were noted in quality-of-life questionnaire scores.…”
Section: 17mentioning
confidence: 99%
See 2 more Smart Citations
“…Kimple et al [5] KEY POINTS Anterior skull-base surgery has become progressively more sophisticated with advances in surgical technique and visualization technology. One major drawback of this technique is the donor-site morbidity it produces at the septum because of exposed cartilage, which can take up to 12 weeks to heal.…”
Section: Skull-base Reconstructionmentioning
confidence: 99%